Development of Corporate Digital Archives in the Industrial Age 4.0 - Faujiah, Ria Rizki; Yanris, Gomal Juni; Pane, Rahmadani (Sinkron : jurnal dan penelitian teknik informatika, 2022)
CV. Ziefa Karya is a company in Labuhanbatu which is engaged in construction contractors who have experience in working on national projects. CV. Ziefa Karya has used computer applications in daily data processing. However, archive storage and management is still done manually. The current filing system can be said to be still less efficient and effective because the incoming and outgoing mail data is often not in accordance with the actual incoming and outgoing mail data. For that we need a solution to overcome this problem. This study aims to build an information system that can be used to manage digital-based archives in CV. Zief Karya. The information system built is web-based. System development using the waterfall model. This research has produced an archive management information system on CV. Ziefa Karya web-based. The result of this research is a website-based mail filing system on CV. Ziefa Karya which has various uses such as data collection of incoming and outgoing letters, details of incoming and outgoing letters, classification of types of letters, disposition of incoming letters, reports of incoming and outgoing letters, and printing of reports of incoming and outgoing letters, as well as printing disposition sheets. Records management information system on CV. Ziefa Karya is able to provide convenience for admins and users in managing digital-based archives. To build a web-based archive information system on CV. Ziefa Karya, development must be carried out by applying the stages in the Waterfall method.